Detailed 40Ar/39Ar Geochronology of the Loyalty and Three Kings Ridges Clarifies the Extent and Sequential Development of Eocene to Miocene Southwest Pacific Remnant Volcanic Arcs. (31st January 2023) - Gans, P. B.; Mortimer, N.; Patriat, M.; Turnbull, R. E.; Crundwell, M. P.; Agranier, A.; Calvert, A. T.; Seward, G.; Etienne, S.; Durance, P. M. J.; Campbell, H. J.; Collot, J.
Abstract: The 2015 VESPA voyage (Volcanic Evolution of South Pacific Arcs) was a seismic and rock dredging expedition to the Loyalty and Three Kings Ridges and South Fiji Basin. In this paper we present 33 40 Ar/ 39 Ar, 22 micropaleontological, and two U/Pb ages for igneous and sedimentary rocks from 33 dredge sites in this little‐studied part of the southwest Pacific Ocean. Igneous rocks include basalts, dolerites, basaltic andesites, trachyandesites, and a granite. Successful Ar/Ar dating of altered and/or low‐K basalts was achieved through careful sample selection and processing, detailed petrographic and element mapping of groundmass, and incremental heating experiments on both phenocryst and groundmass separates to interpret the complex spectra produced by samples having multiple K reservoirs. The 40 Ar/ 39 Ar ages of most of the sampled lavas, irrespective of composition, are latest Oligocene to earliest Miocene (25–22 Ma); two are Eocene (39–36 Ma). The granite has a U/Pb zircon age of 23.6 ± 0.3 Ma. 40 Ar/ 39 Ar lava ages are corroborated by microfossil ages from associated sedimentary rocks. The VESPA lavas are part of a >3, 000 km long disrupted belt of Eocene to Miocene subduction‐related volcanic rocks. The belt includes arc rocks in Northland New Zealand, Northland Plateau, Three Kings Ridge, and Loyalty Ridge and, speculatively, D'Entrecasteaux Ridge. This belt is the product of superimposed Eocene and Oligocene‐Miocene remnant volcanic arcs that were stranded along and near the edge of Zealandia while still‐active arc belts migrated east with the Pacific trench. Plain Language Summary: Samples of lava from the seabed between New Zealand and New Caledonia have been dated using atomic clocks and fossils. Most lavas erupted in a big pulse of volcanic activity between 25 and 22 million years ago. They are part of a belt of now‐extinct undersea volcanoes that stretches for more than 3, 000 km between New Zealand and the Solomon Islands. These volcanoes were formed by subduction of the Pacific Plate under the Australian Plate. Key Points: A major pulse of 25–22 Ma volcanism is documented on the Loyalty and Three Kings Ridges, southwest Pacific Ocean The ridges are part of a more than 3, 000 km long belt of Eocene to Miocene remnant volcanic arcs, stranded along the edge of Zealandia With care in sample selection, and petrological work, meaningful Ar/Ar ages can be obtained from altered and/or very low‐K submarine basalts